Potassium phosphite primes defense responses in potato against - Machinandiarena, M.F. (2012)
Although phosphite is widely used to protect plants from pathogenic oomycetes on a wide range of horticultural crops, the molecular mechanisms behind phosphite induced resistance are poorly understood. The aim of this work was to assess the effects of potassium phosphite (KPhi) on potato plant defense responses to infection with Phytophtora infestans (Pi). Pathogen development was severely restricted and there was also an important decrease in lesion size in infected KPhi-treated leaves. We demonstrated that KPhi primed hydrogen peroxide and superoxide anion production in potato leaves at 12 h post-inoculation with Pi. Moreover, the KPhi-treated leaves showed an increased and earlier callose deposition as compared with water-treated plants, beginning 48 h after inoculation. In contrast, callose deposition was not detected in water-treated leaves until 72 h after inoculation. In addition, we carried out RNA gel blot analysis of genes implicated in the responses mediated by salicylic (SA) and jasmonic acid (JA). To this end, we examined the temporal expression pattern of StNPR1 and StWRKY1, two transcription factors related to SA pathway, and StPR1 and StIPII, marker genes related to SA and JA pathways, respectively. The expression of StNPR1 and StWRKY1 was enhanced in response to KPhi treatment. In contrast, StIPII was down regulated in both KPhi- and water-treated leaves, until 48 h after infection with Pi, suggesting that the regulation of this gene could be independent of the KPhi treatment. Our results indicate that KPhi primes the plant for an earlier and more intense response to infection and that SA would mediate this response.